From Web to workplace designing open hypermedia systems - Grønbaek, Kaj (MIT Press, 1999)
In this book Kaj Gronbaek and Randall H. Trigg present a set of principles for the design of open hypermedia systems and provide concrete implications of these principles for issues ranging from data structures to architectures and system integration and for settings as diverse as the World Wide Web and the workplace.
Keywords: Interactive multimedia.; World Wide Web.; elektronické knihy; electronic books